DESAIN PRODUK INDUSTRI: DINAMO BLDC SEBAGAI KOMPONEN ALTERNATIF UNTUK KONVERSI KE MOTOR LISTRIK - Fajar Maulana; Pinto Anugrah; Ramanda Rizky (Universitas Negeri Malang, 2026)
The ever growing global attention to environmental issues and the urgent need to reduce greenhouse gas emissions has highlighted the importance of reducing dependence on fossil fuels, especially in the transportation sector. Meanwhile, this research highlights the potential of converting oil-fueled vehicles to electric motors, with a focus on Brushless Direct Current (BLDC) dynamos as an environmentally friendly and efficient solution. Electric motors, especially those using Brushless Direct Current (BLDC) dynamos, offer advantages in terms of energy efficiency and reduced emissions. BLDC dynamos, which convert electrical energy from batteries into mechanical motion without the need for carbon brushes, exhibit high efficiency and good durability. However, challenges in designing BLDC dynamos include proper material selection, integration with conversion systems, as well as safety, maintenance, and manufacturing cost aspects. This research identifies and addresses these challenges through a comprehensive design, involving material selection, design of components such as the stator and rotor, and integration of the wiring system. The results show that a good BLDC dynamo design can improve the efficiency and reliability of electric motors, supporting the transition towards more environmentally friendly and sustainable technologies in the transportation sector.